Insulin-like growth factor-1 signaling in the tumor microenvironment: Carcinogenesis, cancer drug resistance, and therapeutic potential - Nwabo Kamdje, Armel H.; Seke Etet, Paul F.; Kipanyula, Maulilio J.; Vecchio, Lorella; Tagne Simo, Richard; Njamnshi, Alfred K.; Lukong, Kiven E.; Mimche, Patrice N. (Frontiers in Endocrinology, 2022)
The tumor microenvironment fuels tumorigenesis and induces the development of resistance to anticancer drugs. A growing number of reports support that the tumor microenvironment mediates these deleterious effects partly by overexpressing insulin-like growth factor 1 (IGF-1). IGF-1 is known for its role to support cancer progression and metastasis through the promotion of neovascularization in transforming tissues, and the promotion of the proliferation, maintenance, and migration of malignant cells. Anti-IGF therapies showed potent anticancer effects and the ability to suppress cancer resistance to various chemotherapy drugs in in vivo and in vitro preclinical studies. However, high toxicity and resistance to these agents are increasingly being reported in clinical trials. We review data supporting the notion that the tumor microenvironment mediates tumorigenesis partly through the IGF-1 signaling pathway. We also discuss the therapeutic potential of IGF-1 receptor targeting, with special emphasis on the ability of IGF-R silencing to overcome chemotherapy drug resistance, as well as the challenges for clinical use of anti-IGF-1R therapies.